The first thing you want to do is combine like terms. This means you should have all the x's on one side and the constants (numbers) on the other side. You can subtract 5x from both sides of the equation and then add 7 to both sides. This gives you -2x=26. Divide both sides be -2 to isolate the variable and your answer is x=-13. Hope this helped!

**Answer:**

L'expression littérale est la suivante

a) La somme de x et 12 b

Solution

X + 12b

b) Le produit de x par 5

Solution

X * 5

c) La différence entre 17 et x

Solution

17-X

d) Le quotient de x par 9

X / 9

**Step-by-step explanation:**

L'expression littérale est la suivante

a) La somme de x et 12 b

Solution

X + 12b

b) Le produit de x par 5

Solution

X * 5

c) La différence entre 17 et x

Solution

17-X

d) Le quotient de x par 9

X / 9

Hi again............. I am glad to help you again.

6x + 35 + 9x = 15x(x+4) -25

6x + 35 + 9x = 15x² + 60x - 25

15x + 35 = 15x² + 60x - 25

Now, we gonna put all the common terms together

15x - 60x + 35 + 25 - 15x² =

-45x + 60 - 15x² = 0

Now, we need to factorize

-15(x-1)(x+4)=0

Set factors equal to 0

x -1 = 0 or x + 4 = 0

**x = 1 or x = 4**

I hope that's help !